SOSIALISASI DIGITAL MARKETING DAN LITERASI KEUANGAN BAGI PELAKU UMKM DI KELURAHAN CIPANENGAH - Ebah Suaebah (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
One of the factors causing low competitiveness of MSMEs is the limitations of business actors in marketing aspects and minimal knowledge about financial literacy. To overcome this, this community service activity aims to introduce MSME products to a wider market, increase competitiveness through the use of digital marketing strategies, and provide education on effective financial management. The approach used in this activity includes socialization, training, and direct assistance to MSME actors in the Cipanengah Village area, Lembursitu District, Sukabumi City. For approximately one month, various activities were carried out in a structured manner. The results of the activities showed that MSME actors began to understand the basic concepts of digital marketing and were able to utilize the internet as a marketing tool. This skill improvement is expected to expand the market reach of partners and strengthen their competitiveness as micro, small, and medium business actors